Essential oils (EOs), pressurized liquid extracts (PLE) and carbon dioxide supercritical fluid extracts (SFE-CO2) from Algerian Thymus munbyanus as valuable sources of antioxidants to be used on an industrial level. (15th September 2018) - Bendif, Hamdi; Adouni, Khaoula; Miara, Mohamed Djamel; Baranauskienė, Renata; Kraujalis, Paulius; Venskutonis, Petras Rimantas; Nabavi, Seyed Mohammad; Maggi, Filippo
Highlights: Thymus munbyanus subsp. coloratus and munbyanus were studied. Essential oils, pressurized liquid and supercritical fluid extracts were obtained. Extracts were examined for total phenolic and antioxidant activities. Pressurized liquid extracts had the strongest antioxidant capacity. Abstract: The aim of this study was to demonstrate the potential of extracts from Algerian Thymus munbyanus as a valuable source of antioxidants for use on an industrial level. To this end, a study was conducted on the composition and antioxidant activities of essential oils (EOs), pressurized liquid extracts (PLE) and supercritical fluid extracts (SFE-CO2 ) obtained from Thymus munbyanus subsp . coloratus (TMC) and subsp . munbyanus (TMM). EOs and SFE-CO2 extracts were analysed by GC-FID and GC×GC-TOFMS revealing significant differences. A successive extraction of the solid SFE-CO2 residue by PLE extraction with solvents of increasing polarity such as acetone, ethanol and water, was carried out. The extracts were evaluated for total phenolic content by Folin–Ciocalteu assay, while the antioxidant power was assessed by DPPH, FRAP, and ORAC assays. SFE-CO2 extracts were also analysed for their tocopherol content. The antioxidant activity of PLE extracts was found to be higher than that of SFE-CO2 extracts, and this increased with solvent polarity (water > ethanol > acetone). Overall, these results support the use of T. munbyanus as a valuable source of substances to be used on an industrial level as preservative agents.